Impact of Social Networking Application TikTok on Student Career Orientation (A Case Study: Students in 3 Majors at Universities in Hanoi City) - Mai Linh, Ngo; Phuong Nam, Tran; Anh, Nguyen Thi Quynh; Hoang Long, Mai (VNU Journal of Science: Policy and Management Studies; Vol 39 No 3, 2023)
More people are using social media to share information nowadays. As a result, the information on social media applications can quickly spread to a large number of individuals. Therefore, social media has become a communication channel that assists employers and businesses in finding and attracting young talent. Vice versa, it also helps people looking for jobs with career orientation. This article will focus on analyzing the main contents of career orientations on TikTok, one of the most popular social media apps today, for students. Alongside the positive aspects of information dissemination, there is still a prevalence of subjective and misleading information regarding careers and job choices on current social media apps. The article will identify the general viewpoints of students on career orientation on TikTok, point out the differences in views among students between three majors, and propose solutions to help them receive selective and accurate career orientation information on social media apps like TikTok. This is a research topic that addresses practical needs as an increasing number of young people today choose social media apps as a place for sharing, learning, and career orientation in the future.